2018
DOI: 10.1111/ipd.12417
|View full text |Cite
|
Sign up to set email alerts
|

Association of breastfeeding and malocclusion in 5‐year‐old children: Multilevel approach

Abstract: Lower prevalence of malocclusion among 5-year-old children was associated with a higher proportion of children breastfed at ages 9 to 12 months at a city level, regardless of sociodemographic factors. These findings highlight the importance of encouraging breastfeeding during a child's first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…Similar results regarding the higher prevalence of anterior open bite and its association with pacifier use were evaluated in a study also conducted in Brazil, in the southeastern region of the country (23) . This association was also confirmed by a systematic review of the literature (24) .…”
Section: Discussionsupporting
confidence: 79%
“…Similar results regarding the higher prevalence of anterior open bite and its association with pacifier use were evaluated in a study also conducted in Brazil, in the southeastern region of the country (23) . This association was also confirmed by a systematic review of the literature (24) .…”
Section: Discussionsupporting
confidence: 79%
“…Malocclusion in the primary dentition is thought to be one indicator for malocclusion in the permanent dentition [ 6 , 7 ]. The prevalence of malocclusion in the primary dentition of preschool children is reported to range from 45.5% to 83.9% based on the criteria for each study, and excessive overjet (10.2–46.1%) and deep overbite (6.05–41.5%) occur with relatively high frequencies [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it has an extremely importance for the development of a normal dental occlusion. Studies have shown a lower proportion of malocclusion in primary dentition in children breastfed up to 12 months 54 or more 55 , regardless the sociodemographic factors. Another advantage of natural breastfeeding clarified in the recent years is that breast milk alone does not cause a decrease in the biofilm pH, suggesting that breastfeeding alone may not contribute to early childhood caries 56 .…”
Section: Discussionmentioning
confidence: 99%